Insurance and racial disparities in prior authorization in gynecologic oncology - Anna Jo Bodurtha Smith; Lakeisha Mulugeta-Gordon; Daniella Pena; Genevieve P. Kanter; Justin E. Bekelman; Ashley Haggerty; Emily M. Ko (Elsevier, 2023)
While prior authorization aims to reduce unnecessary care, it may limit or delay medically necessary care. Delays in cancer care can impact survival and are more common in historically-marginalized populations. Our objective was to examine to what extent disparities occurred in prior authorizations for gynecologic oncology. Using electronic medical records, we performed a retrospective review of prior authorization occurrence during gynecologic oncology care and analyzed the association with patient race and insurance in a multivariate regression model. In this cohort of 1,406 patients treated at an academic gynecologic oncology practice, patients with Medicare Advantage and patients of Asian descent were more likely to experience prior authorization. Addressing insurance-mediate disparities, such as in the occurrence of prior authorization, may help reduce disparities in gynecologic cancer care.